The long roots of formalism in Brazil - Martins, Luiz Renato (Historical Materialism Book Ser., 2017)
The present studies on Brazilian modern art seek to specify some of the dominant contradictions of capitalism's combined but uneven development as these appear from the global 'periphery'. The grand project of Brasilia is the main theme of the first two chapters, which treat the `ideal city' as a case study in the ways in which creative talent in Brazil has been made to serve in the reproduction of social iniquities whose origins can be traced back to the agrarian latifundia. Further chapters scrutinise the socio-historical basis of Brazilian art, and develop, against the grain of the most prominent art historical approaches to modern Brazilian culture, a critical approach to the distinctly Brazilian visual language of geometrical abstraction. The book contends that, from the fifties up to today, formalism in Brazil has expressed the hegemony of the market.